A model for effective partnership working to support programme evaluation. (July 2022) - Fynn, Judith F.; Milton, Karen; Hardeman, Wendy; Jones, Andy P.
The use of multi-agency partnerships, including research-practice partnerships, to facilitate the development, implementation and evaluation of public health interventions has expanded in recent years. However, gaps remain in the understanding of influences on partnership working, and their capacity to facilitate and use evaluation, as well as the characteristics which lead to partnership effectiveness. We applied qualitative methods to explore experiences of stakeholders who were involved in partnerships to deliver and evaluate a national physical activity programme. We combined thematic and network analysis, and drew on concepts of evaluation use, knowledge exchange and organisational systems to interpret our findings and develop a conceptual model of the relationships between partnership characteristics and processes. Our model identifies key partnership characteristics such as high levels of engagement, regular communication and continuity. Furthermore, it highlights the importance of implementing organisational structures and systems to support effective partnership working, knowledge exchange and capacity building.